2019
DOI: 10.2131/jts.44.213
|View full text |Cite
|
Sign up to set email alerts
|

Some non-sensitizers upregulate CD54 expression by activation of the NLRP3 inflammasome in THP-1 cells

Abstract: The human cell line activation test (h-CLAT) is a skin sensitization test that measures the expression of cell surface proteins CD86 and CD54 to evaluate the skin sensitization potential of test chemicals. However, some skin irritants have been reported to induce dramatically high CD54 expression leading to false-positive h-CLAT results. Furthermore, CD54 expression is strongly induced by cytokines, such as interleukin (IL)-1β and tumor necrosis factor (TNF)-α, or danger signals that activate its signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Rossol et al provided evidence that increased extracellular Ca 2+ ions can activate the NLRP3 inflammasome, which plays a role in controlling skin sensitization [30] in monocytes [31]. Mitachi et al reported that the NLRP3 inflammasome is involved in the upregulation of CD54 expression in THP-1 cells [32]. Corresponding to these published data, our results revealed that high Ca 2+ in the KI medium may enhance CD54 expression in THP-1 cells.…”
Section: Discussionsupporting
confidence: 84%
“…Rossol et al provided evidence that increased extracellular Ca 2+ ions can activate the NLRP3 inflammasome, which plays a role in controlling skin sensitization [30] in monocytes [31]. Mitachi et al reported that the NLRP3 inflammasome is involved in the upregulation of CD54 expression in THP-1 cells [32]. Corresponding to these published data, our results revealed that high Ca 2+ in the KI medium may enhance CD54 expression in THP-1 cells.…”
Section: Discussionsupporting
confidence: 84%
“…5). It was reported that salicylic acid induced an increase in CD54 expression in THP-1 cells by activation of NLRP3 inflammasomes (Mitachi et al, 2019). Considering that these positive results for sodium lauryl sulfate and salicylic acid appear to relate to different key events of skin sensitization, the relevance of the false-positive results in our study is unclear.…”
Section: The Dose-effect Relationship Of Cd69 Expression and Cell Viabilitymentioning
confidence: 60%
“…Another functional lymphocyte marker CD54 (ICAM-1) correlated with the severity of the inflammatory process, because CD54 expression is known to be induced by such cytokines as interleukin IL-1β and TNFα [14]. In patients with infectious inflammatory process, the number of CD54 + cells was consistently increased by almost 2-fold in comparison with the reference values (to 10.37±0.42% vs 5.49±0.98% in controls).…”
Section: Innate Immunity Systemmentioning
confidence: 99%